2022
DOI: 10.14814/phy2.15261
|View full text |Cite
|
Sign up to set email alerts
|

The mechanistic and prognostic implications of heart rate variability analysis in patients with cirrhosis

Abstract: Chronic liver damage leads to scarring of the liver tissue and ultimately a systemic illness known as cirrhosis. Patients with cirrhosis exhibit multi-organ dysfunction and high mortality. Reduced heart rate variability (HRV) is a hallmark of cirrhosis, reflecting a state of defective cardiovascular control and physiological network disruption. Several lines of evidence have revealed that decreased HRV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 138 publications
0
8
0
Order By: Relevance
“…Several mechanisms have been shown to be responsible for the blunted responsiveness to vasoconstrictors in advanced cirrhosis (Dümcke and Møller, 2008). It appears that both shear stress in response to portal hypertension and endotoxemia due to portocaval shunt stimulate the release of vasodilators such as nitric oxide, which reduces noradrenalineinduced vasodilation in cirrhosis (Iwakiri and Kim, 2015;Abid and Mani, 2022). This, at least in theory, can impair rhythmic oscillatory vasomotion in the skin in patients with severe physiological network disruption and explain the reduced short-term PTV in non-survivors with liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms have been shown to be responsible for the blunted responsiveness to vasoconstrictors in advanced cirrhosis (Dümcke and Møller, 2008). It appears that both shear stress in response to portal hypertension and endotoxemia due to portocaval shunt stimulate the release of vasodilators such as nitric oxide, which reduces noradrenalineinduced vasodilation in cirrhosis (Iwakiri and Kim, 2015;Abid and Mani, 2022). This, at least in theory, can impair rhythmic oscillatory vasomotion in the skin in patients with severe physiological network disruption and explain the reduced short-term PTV in non-survivors with liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the assessment of organ system connectivity in patients with liver disease has two key benefits, firstly, it provides physiological insight into the complexity of the underlying pathophysiology (e.g., understanding the mechanism of autonomic dysfunction in cirrhosis). Secondly, it also yields crucial prognostic information which can be used chiefly during pivotal organ allocation protocols conducted prior to liver transplantation (Abid and Mani, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians readily acknowledge the functional connectivity of the liver with other organs, which is particularly evident in patients with liver failure who manifest involvement of multiple organs, such as neural, cardiovascular, renal, and metabolic dysfunction, as well as acid/base and electrolyte imbalance [9]. Chronic liver failure (cirrhosis) is associated with impaired cardiovascular control [10][11][12] and thermoregulatory dynamics [13][14][15]. The application of a network approach in patients with cirrhosis has also revealed that organ system network disruption is associated with a poor prognosis in patients with chronic liver failure [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Interestingly, a recent review underlined the importance of the link existing between HRV and inflammation in cirrhosis prognosis. 15 The authors concluded, that HRV analysis has modified the scenario of prognosis assessment in patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…The interest of the research in finding inflammatory biomarkers, potentially used as an indirect measure of HVPG, is based on the fact that portal hypertension is intimately linked to liver damage and fibrosis and these, in turn, are connected to the activation of specific inflammatory pathways 13,14 . Interestingly, a recent review underlined the importance of the link existing between HRV and inflammation in cirrhosis prognosis 15 . The authors concluded, that HRV analysis has modified the scenario of prognosis assessment in patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 99%